Evaluation of Antifreeze Proteins on Miniature Pig Sperm Viability, DNA Damage, and Acrosome Status during Cryopreservation - Daeyoung Kim (The Korean Society of Animal Reproduction and Biotechnology, 2016)
The cryopreservation of sperm has become the subject of research for successful artificial insemination technologies. Antifreeze proteins (AFPs), one of the factors necessary for effective cryopreservation, are derived from certain Antarctic organisms. These proteins decrease the freezing point of water within these organisms to below the temperature of the surrounding seawater to protect the organism from cold shock. Accordingly, a recent study found that AFPs can increase the motility and viability of spermatozoa during cryopreservation. To evaluate this relationship, we performed cryopreservation of boar sperm with AFPs produced in the Arctic yeast Leucosporidium sp. AFP expression system at four concentrations (0, 0.01, 0.1, and 1 μg/ml) and evaluated motility using computer assisted sperm analysis. DNA damage to boar spermatozoa was measured by the comet assay, and sperm membrane integrity and acrosome integrity were evaluated by flow cytometry. The results showed that motility was positively affected by the addition of AFP at each concentration except 1 μg/ml (p<0.001). Although cryopreservation with AFP decreased the viability of the boar sperm using, the tail DNA analyses showed that there was no significant difference between the control and the addition of 0.1 or 0.01 μg/ml AFP. In addition, the percentage of live sperm with intact acrosomes showed the least significant difference between the control and 0.1 μg/ml AFP (p<0.05), but increased with 1 μg/ml AFP (p<0.001). Our results indicate that the addition of AFP during boar sperm cryopreservation can improve viability and acrosome integrity after thawing.